Accounting versus real production responses among firms to tax incentives: Bunching evidence from Hungary - Pálma Mosberger (Magyar Nemzeti Bank, 2016)
Existing evidence indicates that companies' reported earnings react to tax incentives, but we do not know whether these are accounting responses, evasion responses or real responses. This paper tests for the responses using a quasi-experimental design of a corporate minimum tax scheme introduced in Hungary in 2007 that widened the tax base only for firms with low reported profit rate (profit as a share of revenue). With a new panel dataset containing administrative tax records on corporations I replicate previous findings on the earnings responses to tax incentives, but also document three additional pieces of evidence that suggest accounting rather than real responses. First, companies reacted too quickly to the change in incentives to reflect real responses: only a half year after the introduction of the reform the data exhibit sharp bunching in the distribution of profit rates in accordance with the new incentives. Second, direct measures of real production responses suggest no significant behavioral reactions. Additional analysis of the reported cost structure of corporations shows large changes only in reported material cost which is the most easily over-reportable item, supporting the reasoning that reported changes are mostly coming from reduced cost over-reporting.
Keywords: D22; H26; H32; 330; taxation; firm behavior; tax evasion and avoidance